Development and Expanded Clinical Applications of the Da Vinci Surgical Robot System in High-Altitude Regions of Mongolia - Liu, Chao; Khaliunaa B, Khaliunaa B; Hai, Hongxing; Nachin, Baasanjav; Batbold B, Batbold B (Journal of Neonatal Surgery, 2025)
Research Context: The high-altitude conditions in Mongolia (average elevation: 1580 meters), characterized by diminished atmospheric pressure, lower temperatures, and reduced oxygen concentration, present operational challenges for the Da Vinci Surgical System. These environmental factors induce power output attenuation in robotic actuators, measurement deviations in sensing components, and compromised thermal management performance. Such technical constraints underscore the imperative for system-level adaptations to ensure the operational precision and procedural safety required for minimally invasive robotic surgery in plateau environments. Research Methodology: (1) The high-altitude-adapted dynamics optimization model for robotic manipulators.(2) barometric compensation algorithm development. (3) systematic formulation of governing equations for cryogenic-resistant material systems and hierarchical thermal dissipation architectures. Research Outcomes:Manipulator Dynamics Model:M(θ)θ¨+C(θ,θ˙)θ˙+G(θ)=τ−D(θ˙)θ.Barometric Compensation Algorithm:PV=nRT ⇒ Vcomp​=V0P0/P. Cryogenic Lubrication and Thermal Management Equations:Qgen​=Qcond​+Qconv​+Qrad​+Qcooling. Research Conclusions: This study theoretically validates the operational feasibility of the Da Vinci Surgical System in Mongolia's high-altitude environments (average 1,580m). The optimized manipulator dynamics, sensor stabilization protocols, and adaptive thermal management systematically demonstrate compliance with plateau surgical requirements, establishing a technical framework for upgrading intelligent surgical equipment in elevated terrains. The deep integration of 5G communication and artificial intelligence (AI) drives cross-disciplinary innovations in clinical application.Clinical Advancements:General Surgery: Cholecystectomy, colorectal tumor. resectionUrology: Radical prostatectomy, partial nephrectomy.Gynecology: Hysterectomy, endometriosis management.Cardiothoracic Surgery: Valvuloplasty, pulmonary procedures.Orthopedics: Articular and spinal interventions.